2014
DOI: 10.1007/s11552-014-9641-y
|View full text |Cite
|
Sign up to set email alerts
|

Excisional Biopsy of Suspected Benign Soft Tissue Tumors of the Upper Extremity: Correlation between Preoperative Diagnosis and Actual Pathology

Abstract: Background Tumors of the upper extremity are common and mostly benign. However, the prevalence of discordant diagnosis of a solid hand tumor is less studied. The objectives of this retrospective study were (1) to determine the proportion of patients with a different (discrepant or discordant) pathological diagnosis compared to the preoperative diagnosis, (2) to determine the prevalence of the types of pathologies encountered at excisional biopsy for suspected benign tumors, and (3) to determine the types of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The most common pathology in our series was giant cell tumor of the tendon sheath. This finding is consistent with results reported in the literature [ 1 3 ]. Giant cell tumors of the tendon sheath usually present as slow-growing lesions localized mostly on the digits, adjacent to the interphalangeal joints (in our series more common on the dorsal side of the digits).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The most common pathology in our series was giant cell tumor of the tendon sheath. This finding is consistent with results reported in the literature [ 1 3 ]. Giant cell tumors of the tendon sheath usually present as slow-growing lesions localized mostly on the digits, adjacent to the interphalangeal joints (in our series more common on the dorsal side of the digits).…”
Section: Discussionsupporting
confidence: 94%
“…Sluijmer et al suggested that the hand surgeon’s preoperative diagnosis without imaging is usually correct prior to excision of a mass in the hand. Discrepant diagnoses are usually benign and do not alter treatment [ 3 ]. These findings support observation as a reasonable option in innocent-looking, slow-growing tumors of the hand; however, this approach is not commonly accepted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions of the upper extremity are common with an estimated 15% of all soft tissue tumors found in the human body localized to the hand. 13,14 Among all benign upper extremity tumors, ganglions are noted to be the most prevalent (50–70%), followed by giant cell tumor of tendon sheath (14%), and mucous cysts (11%). 15 The risk of an upper extremity lesion being malignant is very low at 1–2% 16,17 for both soft tissue tumors 18 and bony tumors.…”
mentioning
confidence: 99%
“…Routine pathologic evaluation of excised specimen has been questioned in many surgical fields including plastic surgery, orthopedic surgery, urology, otolaryngology, and general surgery. 14,6,7,13,21–27 Previous works have uniformly found that routine surgical pathology diagnosis did not change the treatment plan and thus concluded the practice neither cost-effective 25 nor cost-beneficial. 14,6,7,13,21–27 In the field of hand surgery, the value of pathology examination of benign tumors of the upper extremity has been investigated in a few case series demonstrating minimal clinical benefit.…”
mentioning
confidence: 99%